Experiences Deploying an Always-on Farm Network - Kapetanovic, Zerina; Vasisht, Deepak; Won, Jongho; Chandra, Ranveer; Kimball, Mark (ACM GetMobile: Mobile Computing and Communications, 2017)
Data-driven techniques for agriculture can help farmers reduce waste, increase farm output and ensure sustainability for the environment. The key enabler for such techniques is an always-on connected IoT system that can sense the different characteristics of the farm and generate short-term and long-term actionable insights for the farmer. Yet building such a system is very challenging due to sparse Internet connectivity and lack of reliable power sources. This is further exacerbated by weather variability that stresses the system in numerous ways. We discuss how we built and deployed Farmbeats in the face of these challenges. We hope our experiences will aid researchers who are beginning to explore deployments in farming or other weakly connected, power-starved scenarios, such as construction, oil fields, mining, and others.